Knowledge and learning in speciality practice. Issue 6 (December 2016) - Spence, Kaye; Sinclair, Lynn; Morritt, Mary Lou; Laing, Sharon; ,
Abstract: Purpose: To describe the working knowledge (knowledge-in-action) of nurses in the speciality of neonatal nursing and understand how they acquire this knowledge to inform strategies for orientation, mentorship, in-service programs and curricula of speciality neonatal programs. A questionnaire consisting of three parts; demographics, questions about outcomes of care and the NICU-BKAT4 knowledge questionnaire. Was distributed to all neonatal nurses in Neonatal Intensive Care Units (NICU) and Newborn Emergency Transport Service (NETS) in New South Wales Australia. Results: Nurses with less than one year speciality experience typically had the lowest NICU-BKAT4 scores and 'critical' knowledge essential for safe practice (p's < .001). Patterns of learning emerged, with the majority (97%) of novice nurses showing a preference for experiential 'on-the-job' learning. Conclusion: This research adds to the understanding of nurses' learning preferences, has implications for speciality nursing education and practice and suggests a review of current educational strategies.